2006
DOI: 10.1158/1535-7163.mct-05-0538
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuropilins in cancer

Abstract: Neuropilins are multifunctional non -tyrosine kinase receptors that bind to class 3 semaphorins and vascular endothelial growth factor. NRP-1 and NRP-2 were first identified for their key role in mediating axonal guidance in the developing nervous system through their interactions with class 3 semaphorins. Growing evidence supports a critical role for these receptors in tumor progression. Neuropilin expression is up-regulated in multiple tumor types, and correlates with tumor progression and prognosis in speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(214 citation statements)
references
References 111 publications
(101 reference statements)
8
200
0
6
Order By: Relevance
“…11,12,14,[22][23][24][25][26] As NRP1 is widely expressed in our derived MDA-MB-231 clones, the effects of VEGF isoforms on survival/apoptosis may involve NRP1. The silencing of NRP1 decreased the apoptosis of clones overexpressing VEGF189 under serum starvation or doxorubicin treatment, and resulted in more necrosis in both conditions than observed for shCtl-transfected V189 clones.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,14,[22][23][24][25][26] As NRP1 is widely expressed in our derived MDA-MB-231 clones, the effects of VEGF isoforms on survival/apoptosis may involve NRP1. The silencing of NRP1 decreased the apoptosis of clones overexpressing VEGF189 under serum starvation or doxorubicin treatment, and resulted in more necrosis in both conditions than observed for shCtl-transfected V189 clones.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…20,21 NRP1 is expressed at high levels in several tumor cells, where it has been implicated in cell migration and survival. 11,12,[22][23][24][25][26][27] Recently, our group showed that VEGF189 binds to NRP1, 10 in addition to VEGF165. However, the role of VEGF189-NRP1 association in survival has not been elucidated.…”
Section: Overexpression Of Vegf189 In Breast Cancer Cells Induces Apomentioning
confidence: 99%
“…Tumors examined 1 h after the injection of FAM-tLyP-1 were strongly fluorescent under blue light (Figure 5a). Normal tissues, which express NRP1 at lower levels than tumors (Ellis, 2006;Guttmann-Raviv et al, 2006;Bagri et al, 2009), were negative, with the exception of the kidneys, which reflects the clearance of the peptide through this organ. A control peptide, FAM-ARALPSQRSR (Laakkonen et al, 2002), did not accumulate in the 4T1 tumors.…”
Section: Lyp-1 Internalization Uses the Cendr Pathwaymentioning
confidence: 99%
“…Wingless/integrated1 (Wnt1) and neuropilin-1 (NRP1) were identified as direct targets for miR-148a (94). Wnt-1 induced Wnt signaling can promote EMT and metastasis (95,96) and NRP1 functions as mediator of cell growth, survival and metastasis (97,98). miR-148b: In a retrospective study, miR-148b and additional 15 miRs were found to be associated with relapse in BC patients (99).…”
Section: Breast Cancer Metastasis Suppressing Mirsmentioning
confidence: 99%